The persistence of NZ dollar misalignments relative to Purchasing Power Parity - Luo, R. H.; Plantier, C. (AUT Faculty of Business, 2003)
This paper examines the Purchasing Power Parity (PPP) relationship between the New Zealand dollar and the Australian dollar, Japanese Yen, the UK sterling, the US dollar and the Trade-Weighted Index respectively, using the ADF and Phillips-Perron unit root tests, Engle-Granger cointegration test and Johansen cointegration test. We use high frequency monthly data running from 1985 to 2001 for the analysis. In addition, this study analyzes the adjustment dynamics of real exchange rates of New Zealand through impulse response analysis and constructs confidence intervals for the half-life persistence estimates based on the simple and bootstrap methods. While the unit root tests and cointegration tests show mixed results for the long-run PPP, there is sufficient evidence that relative price levels help determine the value of the NZ dollar in the medium term. In particular, the point estimates and the confidence intervals of the half-life persistence estimates are found to be significantly lower than previous studies, 1-3 years compared with 3-5 years. Moreover, the half-life of PPP reversion between New Zealand and Australia is less than 1 year, which suggests that misalignments between NZ and AU dollar are not very persistent.